Agir seul en justice : du droit au choix — État de la jurisprudence sur les droits des justiciables non représentés - Laniel, Richard-Alexandre; Bahary-Dionne, Alexandra; Bernheim, Emmanuelle (Les Cahiers de droit, 2018)
Québec courts are experiencing an increase in the number of parties without legal representation. Although this trend is generally presented as a problem that generates extra costs and delays for the courts, the central issue is clearly that a large segment of the population is unable to afford legal expenses. However, what is the legal status of non-representation : is acting alone a right ? Although this is the approach generally taken by the courts, the extent of the right is strongly limited by the discretionary way it is implemented. An important distinction must be made between criminal and civil cases, in particular concerning protection for a right that is constitutional in criminal cases, but legislative in civil cases. Despite the lack of knowledge about the reasons why people choose not to be represented by a lawyer, a survey of the jurisprudence shows that acting alone is often considered to be a choice, which then has a significant effect on the implementation of the related judicial guarantees.